Features of Internet fraud during the pandemic COVID-19 - Metelskiy, Ihor (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The scientific article is devoted to the study of the relevance of the issue of the spread of offenses on the Internet, which is an extremely relevant issue in the conditions of the development of modern society, especially during the global pandemic of COVID-19. This problem necessitates the study and research of the essence of cyber fraud as one of the most common criminal offenses committed in the global network and the features of its commission. Moreover, the problem of protecting Internet users both during work and during leisure time is more acute than ever. In particular, it is important to note the constituent elements of fraud on the Internet, as they express the peculiarities of the essence of this type of offense. In addition, the work highlights issues related to the cybercriminal and his criminological features, which, in particular, is important for the detection and prevention of cyberfraud. The prevalence of fraud on the Internet, depending on the age and gender of the offenders, also needs attention. Separately, it is worth noting the study of the problem of victims of cyber fraud, which again allows us to understand the prevalence of cyber fraud among Internet users. Recommendations for preventing and combating this type of crime were also made.